Benefit of one baja fertilizer for attaining agricultural sustainability among malaysian paddy farmers: Agricultural sustainability among Malaysian paddy farmers - Adnan, N. (IGI Global, 2016)
Green technology is the means of improving towards the rising environmental concern. An implication of One BAJA fertilizer is the need for the modern development in agricultural industry. The main objective of this study was to identify the marketing strategies on One BAJA fertilizer among Malaysian Paddy farmers. Based on B2B market segmentation, or in other words industrial market segmentation, for the One Baja Fertilizer of Commerce in Malaysia. One Baja Fertilizer markets in Malaysia operations cover the need of green fertilizer among Malaysia paddy farmers. The study is considered to be a pretty reliable source of information for One Baja Fertilizer among Malaysian paddy farmers. A continuous collection of information is required for completing the market strength and weakness. One Baja Fertilizer operations were concluded to be pretty successful, though a few services should be terminated for not being profitable and improvements in the organization's operations and structure should be realized in order to better cover all market segments present at One Baja Fertilizer. Â© 2017 by IGI Global.